Contesting Modernization in Rural Peripheral Settings: Green Revolution, Women and Entangled Paradigms under the Pioneering Lens of Cynthia Hewitt de Alcántara - Ruvituso, Clara (2022)
The interdependent inequalities in the production and circulation of knowledge in the social sciences have marked the historical development of mostly male canons from the centers, to the detriment of the voices of women and production from the peripheries. With the impulse of the feminist wave in Latin America, the contribution of women to the construction of the social sciences in the global south has begun to have greater relevance. This article introduces for the first time the intellectual and professional trajectory of the sociologist Cynthia Hewitt de Alcántara from the gender and sociology of knowledge perspectives. Based on her written production and an in-depth interview, I focus on the author’s production during her first stay in Mexico between 1966-1985, reconstructing the interrelations between the contexts of production and her pioneering contributions contesting modernization processes within the green revolution, the situation of women in peripheral rural contexts and the entangled paradigms of the social sciences.